JENIS-JENIS PAKU TERESTERIAL DI HUTAN BUKIT BARISAN DESA HALALANG NAGARI KAMANG MUDIAK KECAMATAN KAMANG MAGEK - AISYAH, AISYAH; ABIZAR, ABIZAR; HERNAWATI, HERNAWATI (STKIP PGRI Sumbar, 2013)
ABSTRAKÂ Ferns are heterogens in terms of his place, there are the kinds of spikes that live on land (terrestrial), there is a ride of his life on other plants (epiphytes), and there are spikes that grow in water (higrofit). Bukit Barisan is a limestone hill forests has the conditions and rock properties that are different from other forest types. The study was conducted by survey method by direct observation and collection. From the research that has been conducted in the Bukit Barisan Forest Jorong Halalang Nagari Kamang Mudiak District Kamang Magek terrestrial obtained 12 types of nails. Nails were found grouped into two namely clasis Filicopsida and Lycopsida, two orders of the Filicalles and Sellaginellales, nine family is Adiantaceae, Dennstaedtiaceae, Gleicheniaceae, Nephrolepidaceae, Pteridaceae, Schizaeceae, Tectariaceae, Thelypteridaceae, Selaginellaceae..Â